Bitcoin, Gold, the Indonesian Stock Market, and Exchange Rate: GARCH Volatility Analysis - Rahmat Siauwijaya; Dewi Sanjung (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2022)
Bitcoin has gained popularity as an investment asset because of its similarity to gold, which sparked the idea that bitcoin can be used as a hedging instrument to the fiat currency exchange rate. This paper aims to analyze bitcoin's volatility and return to gauge its feasibility as an investment asset, and hedging tool for the USD-IDR exchange rate with the GARCH and EGARCH models. With data on the daily closing price of bitcoin, gold, IDX composite index, and USD-IDR exchange rate from January 1, 2016, to December 31, 2020, the study attempts to find factors affecting bitcoin returns with the independent variables of bitcoin’s price, gold, and USD-IDR exchange rate by estimating their correlation. Following the analysis, this study shows that the volatility of USD-IDR exchange rates negatively influences bitcoin returns, making it a relatively safe investment asset. Additionally, the study found that bitcoin returns are not affected by the variables of gold price and the IDX composite index. However, we found that the USD-IDR exchange rate significantly affects bitcoin returns, while gold price and bitcoin’s price does not significantly affect bitcoin returns. Further, the analysis found that bitcoin is unsuitable for hedging due to its sensitivity to asymmetric shocks.